Comparison of magnetic nanoparticle and microwave hyperthermia cancer treatment methodology and treatment effect in a rodent breast cancer model. (12th November 2013) - Petryk, Alicia A.; Giustini, Andrew J.; Gottesman, Rachel E.; Trembly, B. Stuart; Hoopes, P. Jack
Abstract: Purpose : The purpose of this study was to compare the efficacy of iron oxide/magnetic nanoparticle hyperthermia (mNPH) and 915 MHz microwave hyperthermia at the same thermal dose in a mouse mammary adenocarcinoma model. Materials and methods : A thermal dose equivalent to 60 min at 43 °C (CEM60) was delivered to a syngeneic mouse mammary adenocarcinoma flank tumour (MTGB) via mNPH or locally delivered 915 MHz microwaves. mNPH was generated with ferromagnetic, hydroxyethyl starch-coated magnetic nanoparticles. Following mNP delivery, the mouse/tumour was exposed to an alternating magnetic field (AMF). The microwave hyperthermia treatment was delivered by a 915 MHz microwave surface applicator. Time required for the tumour to reach three times the treatment volume was used as the primary study endpoint. Acute pathological effects of the treatments were determined using conventional histopathological techniques. Results : Locally delivered mNPH resulted in a modest improvement in treatment efficacy as compared to microwave hyperthermia ( p  = 0.09) when prescribed to the same thermal dose. Tumours treated with mNPH also demonstrated reduced peritumoral normal tissue damage. Conclusions : Our results demonstrate similar tumour treatment efficacy when tumour heating is delivered by locally delivered mNPs and 915 MHz microwaves at the same measured thermal dose. However, mNPH treatments did not result in the same type or level of peritumoral damage seen with the microwave hyperthermia treatments. These data suggest that mNP hyperthermia is capable of improving the therapeutic ratio for locally delivered tumour hyperthermia. These results further indicate that this improvement is due to improved heat localisation in the tumour.